Suomalainen teollinen internet - haasteesta mahdollisuudeksi: Taustoittava kooste; Industrial Internet Transforms Finland's Challenges into Opportunities: Background Synthesis - Jari Juhanko; Marko Jurvansuu; Heikki Ailisto; Petteri Alahuhta; Jari Collin; Marco Halen; Tapio Heikkilä; Helena Kortelainen; Martti Mäntylä; Timo Seppälä; Mikko Sallinen; Magnus Simons; et al. (The Research Institute of the Finnish Economy (ETLA), 2015)
– The industrial internet has been described as a new industrial revolution, a significant re-shaper of markets and a global impetus for growth. Finland is looking for new growth opportunities and competitive edge in the industrial internet. The Prime Minister's Office has identified it as one of its key themes. This project is run by VTT Technical Research Centre of Finland, Aalto University and ETLA, the Research Institute of the Finnish Economy. The Finnish industrial internet – from challenge to opportunity is a project which will carry out an extensive evaluation of the grand scheme of internet economics, clarifying its social and economic impacts both within Finland and globally, while focusing on Finnish manufacturing industry. Furthermore, the project will cover other critical areas of business life (such as energy, transport and logistics, trade, property and infrastructure) as well as the functioning of the public sector. Finland has all the prerequisites for success: a competitive and international technology industry, solid ICT skills, and a public sector that is well-managed and capable of reform. The Finnish industrial internet – from challenge to opportunity project will produce suggestions for policy and measures that would enable Finnish society and Finnish industry to best create and capture value added from this opportunity. This report serves as a background synthesis for the theme.
Keywords: L6; L86; L8; 330; Industrial internet; Disruption; Automation; Digitalization; Competitiveness; Industry; Computerunterstützung; Industrie; Internationaler Wettbewerb; Finnland